DEVELOPING INTENS (INTERACTIVE ENGLISH) BOOK FOR ADVANCE LEARNERS - iin baroroh ma'arif; Ulfa Wulan Agustina; Nisrina Nur Vieda Fitri (Universitas Muria Kudus, 2021)
The purpose of this research is developing English learning media called INTENS (Interactive English) for advance learners. This media consist of some materials which is appropriate to be studied for all English advance learners. The research method used is Research and Development. This development used Borg and Gall theory which have several steps, those are; 1) Research and Information Collection, 2) Planning, 3) Develop Preliminary Form of Product, 4) Preliminary Field Testing, 5) Main Product Revision, 6) Main Field Testing 7) Final Product Revision 8) Dissemination and Implementation. The media validation result got 95 score it was in “very good” category, and the material validation got 92 score it was in “very good” category. Subject of this research was students of MA Al Bairuny Jombang. The students’s responses of try out result 85 was in “good category”. It can be concluded that INTENS (Interactive English) is feasible to be used as a learning media for English advance learners.